2019
DOI: 10.3389/fpls.2019.00798
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cadmium Risk to the Photosynthetic Performance of Hybrid Pennisetum

Abstract: Photosynthesis plays an essential role in plant growth and crop yield, and the mechanisms of the effects of cadmium (Cd) on photosynthetic performance require more attention. The acute toxicity of Cd in soil to the photosynthetic capacity of Hybrid Pennisetum was evaluated using gas exchange parameters, A / C i curves, light response curves, and chlorophyll a fluorescence transients after exposure to ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(41 citation statements)
references
References 106 publications
2
36
0
Order By: Relevance
“…In our current experiment, photosynthetic attributes and pigments were reduced in pigeon pea under different cadmium treatments (Table 2). Our results are consistent with previous findings, where similar reduced photosynthetic attributes have been observed in other plant species [24,55,56,59].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our current experiment, photosynthetic attributes and pigments were reduced in pigeon pea under different cadmium treatments (Table 2). Our results are consistent with previous findings, where similar reduced photosynthetic attributes have been observed in other plant species [24,55,56,59].…”
Section: Discussionsupporting
confidence: 94%
“…Cadmium reduces stomatal density, decreases stomatal pore size, and affects its normal opening and closing mechanism [21,55,56]. Cadmium ions disturb the thylakoid membrane chain and thus decrease rubisco efficiency in carbon fixation [24,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence parameters of chlorophyll, including the primary light energy conversion efficiency ( F v / F m ), non-photochemical quenching coefficient ( q N ), photochemical quenching coefficient ( q P ), and effective quantum yield of PSII photochemistry ( Φ PSII), were measured by an FMS2 portable fluorescence system (Hansatech instruments, King’s Lynn, Norfolk, United Kingdom). The F v / F m determination required leaves to be dark-adapted for half an hour ( Song et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The main reason for this result may be that the host selected was different (Klichowska et al 2019). There was research also indicated that the decrease of photosynthesis under Cd stress was related to the decrease of carboxylase and ribose 1, 5diphosphate carboxylase activities (Song et al 2019). However, the application of S. indica enhanced Gs, Pn, Tr of soybean (Table 2).…”
Section: Assessment Of Heavy Metal Pollution In Soilmentioning
confidence: 99%